ANALISIS KEPUASAN PELANGGAN DENGAN PENDEKATAN SERVICE QUALITY (SERVQUAL) Studi pada Bank BRI Cabang Yogyakarta-Cik Di Tiro - , Yuli Ristina ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Financial statements published by the company, which is one source of information regarding the company's financial position, performance and changes in financial position of the company is very handy in making the right decision. So the information presented is more helpful in decision-making, financial data must be converted first so the information can be useful in making economic decisions. One of the information used to make appropriate investment decisions is a cash flow statement. The purpose of research is to analyze the cash flow ratio in predicting the failure of a company listed on the Indonesia Stock Exchange by way of analysis of each company's ratio of cash flow before delisting period. The data used is the data taken from the listed companies in Indonesia Stock Exchange as much as 20 during the period 2004 to 2007. Logistic regression method is used to obtain four cash flow ratios to predict bankruptcy that is the ratio of the components of cash sources, the ratio of cash from operations, finance policies ratio and the ratio of operating cash.